Content of food aditives according NOVA food classification in edible products adversited on colombian television in 2018 (2020)
ABSTRACT: Introduction: The use of additives is increasingly common in the food industry. In turn, multiple studies show that a large amount of ultra-processed edible products are advertised on television. There is a lack of evidence in Colombia about the content of additives present in these products.Objectives: This paper aims: 1) describe the percentage of edible products according NOVA food classification [I)natural or minimally processed foods, II) culinary ingredients, III) processed foods and IV) ultra-processed products], 2) comparing the amount of additives present innon-ultra-processed foods (NUPF) vs ultra-processed edible products (UPF), and 3) compare the content of food additives in NUPF vs UPF.